Monetary Union Feasibility in the East African Community: Evidence from GPPP - Redda, Ephrem Habtemichael; Muzindutsi, Paul-Francois (International Journal of Economics and Financial Issues, 2021)
This study utilises the generalised purchasing power parity (GPPP) to assess the feasibility of a monetary union in the East African Community (EAC) region. Time series and panel vector error correction models (VCM) were used to analyse monthly data from 1996-2016 for the five EAC countries. The cointegration results support the existence of a long-run relationship between the tested variables, providing evidence for the optimum currency area (OCA) and the feasibility of monetary union in the EAC region. The VECM results indicate some differences in the size of the coefficients, suggesting that any change/shock of real exchange rate in the region may cause unintended currency flow from one country to the other in the short run, and this may constrain the possibility of an effective and efficient monetary union. Therefore, member countries should harmonise their monetary policies well ahead of the implementation of the monetary union the region. Keywords: East African Community, Monetary Union, GPPP, Optimum Currency Area. JEL Classifications: E42, F15, F31, F36, F45 DOI: https://doi.org/10.32479/ijefi.11846